2020
DOI: 10.3390/antibiotics9090633
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Disulfiram (Tetraethylthiuram Disulfide) as a Potential Drug Candidate against Borrelia burgdorferi In Vitro and In Vivo

Abstract: Lyme disease caused by the Borrelia burgdorferi (Bb or B. burgdorferi) is the most common vector-borne, multi-systemic disease in the USA. Although most Lyme disease patients can be cured with a course of the first line of antibiotic treatment, some patients are intolerant to currently available antibiotics, necessitating the development of more effective therapeutics. We previously found several drugs, including disulfiram, that exhibited effective activity against B. burgdorferi. In the current study, we eva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…In vitro, Alvarez-Manzo et al [29] found disulfiram to be less effective than drugs like clarithromycin and nitroxoline at 5 µg/mL (16.9 µM), while Pothineni et al found disulfiram be extremely effective at its minimum bactericidal concentration of 1.25 µM (0.371 µg/mL) [17], and Potula et al found disulfiram to decrease in efficacy in concentrations greater than 5 µM (1.48 µg/mL). Together, these conclusions suggest that disulfiram becomes less effective at higher concentrations, which is supported by the fact that colloidal forms of disulfiram arise at higher concentrations [22]. Potula et al also provide evidence from in vivo murine experiments that disulfiram was able to clear B. burgdorferi in 28 days post-infection, suppress cardiac inflammatory responses, and reduce the amount of antibody produced [22].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In vitro, Alvarez-Manzo et al [29] found disulfiram to be less effective than drugs like clarithromycin and nitroxoline at 5 µg/mL (16.9 µM), while Pothineni et al found disulfiram be extremely effective at its minimum bactericidal concentration of 1.25 µM (0.371 µg/mL) [17], and Potula et al found disulfiram to decrease in efficacy in concentrations greater than 5 µM (1.48 µg/mL). Together, these conclusions suggest that disulfiram becomes less effective at higher concentrations, which is supported by the fact that colloidal forms of disulfiram arise at higher concentrations [22]. Potula et al also provide evidence from in vivo murine experiments that disulfiram was able to clear B. burgdorferi in 28 days post-infection, suppress cardiac inflammatory responses, and reduce the amount of antibody produced [22].…”
Section: Discussionmentioning
confidence: 94%
“…Together, these conclusions suggest that disulfiram becomes less effective at higher concentrations, which is supported by the fact that colloidal forms of disulfiram arise at higher concentrations [22]. Potula et al also provide evidence from in vivo murine experiments that disulfiram was able to clear B. burgdorferi in 28 days post-infection, suppress cardiac inflammatory responses, and reduce the amount of antibody produced [22].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, to reduce the amount of 5-FU required, a co-drug was incorporated to produce a synergistic effect and increase safety and the efficacy of the formulation [19]. One approach to expedite the development of novel formulations is to repurpose pre-existing drugs that have been approved for the treatment of other medical conditions [20]. Disulfiram (DSF), a drug currently used in the treatment of chronic alcoholism, has been shown to possess anti-tumor activity [21].…”
Section: Introductionmentioning
confidence: 99%
“…Judging according to published scientific literature, disulfiram seems to be promising treatment for conditions as distinct as Alzheimer's disease (Reinhardt et al, 2018), obesity (Bernier et al, 2020, tuberculosis (Dalecki et al 2015), lyme borreliosis (Potula et al, 2020), and even for current pandemic. Indeed, two recent studies in Nature and Nature Immunology suggest that disulfiram could treat covid-19 (Jin et al, 2020) and sepsis (Hu et al, 2020), respectively.…”
mentioning
confidence: 99%